If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7.5 + 0.5x = 3x + 1.5 Reorder the terms: 7.5 + 0.5x = 1.5 + 3x Solving 7.5 + 0.5x = 1.5 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 7.5 + 0.5x + -3x = 1.5 + 3x + -3x Combine like terms: 0.5x + -3x = -2.5x 7.5 + -2.5x = 1.5 + 3x + -3x Combine like terms: 3x + -3x = 0 7.5 + -2.5x = 1.5 + 0 7.5 + -2.5x = 1.5 Add '-7.5' to each side of the equation. 7.5 + -7.5 + -2.5x = 1.5 + -7.5 Combine like terms: 7.5 + -7.5 = 0.0 0.0 + -2.5x = 1.5 + -7.5 -2.5x = 1.5 + -7.5 Combine like terms: 1.5 + -7.5 = -6 -2.5x = -6 Divide each side by '-2.5'. x = 2.4 Simplifying x = 2.4
| 28=(16)-(4x) | | 3x(20-x)= | | -3+1=4*3-5-3*3 | | -14x+7y=-21 | | y-16=.25 | | -9x+30=-12 | | 8y^2+6y-35=0 | | -x-5=-2 | | X+(2X)+(X+2ft)=70 | | 10m+5=5 | | -x-2=-5 | | 9-2x=6x-15 | | 3(x-0.5x)-2x=132 | | .33=h+.4 | | 165u-4= | | 68-2x=79-3x | | t-23.5=39.7 | | 36=(8)-(14x) | | 0.05m=13.80 | | 9.2=-5g-23.3 | | (-3x)-(7)=23 | | 65-x=180 | | 9+2x=49 | | (-3x)-(7)=3 | | [5x]-7=14 | | abs(5x-4)=-6 | | 9x-4=72 | | 15m+6.3=9.8 | | abs(5x-4)=6 | | Y=7.5+0.5x | | 12y=-48+4x | | 4+12x=112 |